Do Israeli health promoting schools contribute to students' healthy eating and physical activity habits?. (4th October 2017) - Hayek, Samah; Tessler, Riki; Bord, Shiran; Endevelt, Ronit; Satran, Carmit; Livne, Irit; Khatib, Mohammed; Harel-Fisch, Yosi; Baron-Epel, Orna
Abstract: The Israeli Health Promoting School Network (HPSN) is actively committed to enhancing a healthy lifestyle for the entire school population. This study aimed to explore the contribution of school participation in the HPSN and students' individual characteristics to healthy eating and physical activity habits among Israeli school children aged 10–12 years. A cross-sectional survey was conducted among 4166 students in grades 4–6 from 28 schools. The schools were selected from a sample of HPSN affiliated and non-HPSN schools. The contribution of individual characteristics (grade, gender and subjective self-reported health education activities at school) and school characteristics (school type, population group, deprivation score) to healthy eating and physical activity habits was analyzed using multi-level hierarchical models. Multi-level analysis indicated that student's individual characteristic was significantly associated with healthy eating and physical activity habits. The subjective self-reported health education received at school was statistically significant factor associated with students' health behaviors. The school's affiliation with the HPSN was not associated with higher healthy eating and physical activity scores after adjusting for individual factors. These findings suggest that Israeli HPSN schools do not contribute to children's health behaviors more than other schools. Therefore, health promoting activities in HPSN schools need to be improved to justify their recognition as members of the HPS network and to fulfill their mission.